Problema invazivnykh mikozovv revmatologii (chast' II) - B S Belov; O N Egorova; G M Tarasova; M V Polyanskaya; R M Balabanova; B S Belov; O N Egorova; G M Tarasova; M V Polyanskaya; R M Balabanova (Современная ревматология, 2010)
Candida genus fungi have been noted to be the most common pathogens of mycotic infections. The extensive use of antimycotics for prevention and empirical therapy is unwarranted, which has resulted in an increase in the frequency of fluconazole-resistant pathogen strains, which is 15-0% in Russia and 50% at some hospitals. The presence of Candida in any organ and tissue has been found to be a risk factor for potentially fatal dissemination and systemic candidiasis. The major forms and clinical manifestations of Candida lesions and the principles of their prevention, diagnosis, and treatment are described.